Emerging Asian real estate investment trust (REIT) portfolio allocation based on property type - Tiong, Chai Ping, 1991- 621481; Janice, Lee Yim Mei, supervisor 530360; Fakulti Geoinformasi dan Harta Tanah 555724 (2015)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah)) - Universiti Teknologi Malaysia, 2015